BEHAVIOR OF GEOPOLYMER CONCRETE WALL PANELS WITH SQUARE OPENING VARIATIONS SUBJECTED TO CYCLIC LOADS - Saloma; Nurjannah, Siti Aisyah; Hanafiah; Usman, Arie Putra; Hu, Steven; Usman, Fathoni (Journal of Applied Engineering Science, 2023)
Masonry walls are non-structural elements that can increase the stiffness and strength of building structures subjected to lateral loads. Reinforced concrete (RC) wall systems are structural elements that have been developed to improve structural performance. Because the use of large amounts of cement in RC is not environmentally friendly, cement-free concrete called geopolymer concrete (GC) has been developed. Research on GC structural beam-column joints and slab joints has proven that GC fulfils the strength requirements for structural elements. However, previous studies have not addressed the performance of reinforced GC wall panels (WPs) under cyclic loads. Therefore, this study filled the gap with the novelty of investigating the performance of reinforced GC structural WPs subjected to cyclic lateral loads. Numerical analysis was used to determine the performance of GC-WPs in resisting cyclic lateral loads, and an aerated concrete wall panel (AC-WP) model was used for verification. The study investigated GC-WPs that were 1500 mm wide and 200 mm thick, varying in solidity such that one was entirely solid (GC-WP1) and two had square openings in horizontal and vertical configurations (GC-WP2 and GC-WP3, respectively). The cyclic loading history referenced FEMA 461. The analysis resulted in hysteretic curves, ductility ratios, and stress contours. GC-WP1 achieved the highest maximum lateral loads (73,994 kN and -67,225 kN) compared to the other GC-WP models, with a high ductility ratio of 14,681. Results show that GC has the potential for use in WPs to improve their resistance to lateral cyclic loads.